2020
DOI: 10.1111/mec.15712
|View full text |Cite
|
Sign up to set email alerts
|

A mobile sex‐determining region, male‐specific haplotypes and rearing environment influence age at maturity in Chinook salmon

Abstract: Variation in age at maturity is an important contributor to life history and demographic variation within and among species. The optimal age at maturity can vary by sex, and the ability of each sex to evolve towards its fitness optimum depends on the genetic architecture of maturation. Using GWAS of RAD sequencing data, we show that age at maturity in Chinook salmon exhibits sex-specific genetic architecture, with age at maturity in males influenced by large (up to 20 Mb) male-specific haplotypes. These region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 98 publications
0
22
0
Order By: Relevance
“…Second, the housefly offers a precedent for movement of a male-determining factor onto the X chromosome [ 42 , 43 ]. Mobile sex-determining regions are also known from other organisms, including Salmonid fish [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the housefly offers a precedent for movement of a male-determining factor onto the X chromosome [ 42 , 43 ]. Mobile sex-determining regions are also known from other organisms, including Salmonid fish [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…McKinney et al. (2021) also documented that age at maturity in Chinook Salmon is governed by sex‐specific genetic architecture. It could be that the phenotype is triggered by the interaction between environmental stimuli, which may vary by population, and the presence of a particular gene or genes.…”
Section: Discussionmentioning
confidence: 99%
“…A different study of Rainbow Trout (the same species as Steelhead Trout) found some genomic regions associated with early maturation that affected both sexes and others that were sex‐specific (Haidle et al, 2008 ). Sex‐specific haplotypes associated with age at maturity have been identified for Chinook salmon (McKinney et al, 2021 ), which would avoid intralocus sexual and tactical conflicts in that species. In Coho salmon, Kodama et al found genomic regions associated with growth and age at maturity affected males and females differently, though statistical power was low due to few families and small sample sizes within families (Kodama et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%